D-dimer levels and characteristics of lymphocyte subsets, cytokine profiles in peripheral blood of patients with severe COVID-19: A systematic review and meta-analysis - Zhang, Haiyue; Wu, Huajun; Pan, Dongli; Shen, Weifeng (Frontiers in Medicine, 2022)
Purpose: A series of complications caused by severe Covid-19 can significantly affect short-term results. Therefore, early diagnosis is essential for critically COVID-19 patients. we aimed to investigate the correlation among D-dimer levels, lymphocyte subsets, cytokines, and disease severity in COVID-19 patients. Methods: Systematic review and meta- analysis of PubMed, Scopus, Web of Science, Cochrane Central Register of Controlled Trials, Embase, clinical trials, and China National Knowledge Infrastructure (CNKI) until 1 August 2022. We considered case-control, and cohort studies that compared laboratory parameters between patients with severe or non-serious diseases or between survivors and non-survivors. Pooled data was assessed by use of a random-effects model and used I² to test heterogeneity. We assessed the risk of bias using the Newcastle- Ottawa Scale. Results: Of the 5561 identified studies, 32 were eligible and included in our analysis (N=3337 participants). Random-effect results indicated that patients with COVID-19 in severe group had higher levels for D-dimer (WMD=1.217mg/L, 95%CI=[0.788, 1.646], P<0.001), neutrophil-to-lymphocyte ratio (NLR) (WMD=6.939, 95%CI=[4.581, 9.297], P<0.001), IL-2 (WMD=0.371pg/ml, 95%CI= [-0.190,0.932], P=0.004), IL-4 (WMD=0.139pg/ml, 95%CI= [0.060, 0.219], P=0.717), IL-6 (WMD=44.251pg/ml, 95%CI= [27.010, 61.493], P<0.001), IL-10 (WMD=3.718pg/ml, 95%CI= [2.648, 4.788], P<0.001) as well as lower levels of lymphocytes (WMD= -0.468( ×109/L), 95%CI= [-0.543, -0.394], P<0.001), T cells(WMD=-446.746(/μL), 95%CI= [-619.607, -273.885], P<0.001), B cells(WMD=-60.616(/μL), 95%CI= [-96.452, -24.780], P<0.001), NK cells(WMD=-68.297(/μL), 95%CI= [-90.600, -45.994], P<0.001), CD3+T cells (WMD=-487.870(/μL), 95%CI= [-627.248, -348.492], P<0.001), CD4+T cells (WMD=-290.134(/μL), 95%CI= [-370.834, -209.435], P<0.001), CD8+T cells(WMD=-188.781(/μL), 95%CI= [-227.806, -149.757], P<0.001). Conclusions:There is a correlation among higher levels of D-dimer, cytokines, lower levels of lymphocyte subsets,and disease severity in COVID-19 patients. These effective biomarkers may help clinicians to evaluate the severity and prognosis of COVID-19. This study is registered with PROSPERO, number CRD42020196659.